2022
DOI: 10.1073/pnas.2200279119
|View full text |Cite
|
Sign up to set email alerts
|

The causal effect of a family planning intervention on women’s contraceptive use and birth spacing

Abstract: Significance Improving access to family planning may promote contraceptive use after childbirth and reduce the likelihood of closely spaced high-risk births; however, empirical evidence for these claims is limited. We present findings from a field experiment that examines the causal impact of a broad-based family-planning intervention on postpartum contraceptive use and fertility over a 2-y period, which allows us to assess impact on high-risk short pregnancy intervals. Our findings demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…After combining these two studies, the meta-analysis showed no significant associations with interventions (OR = 0.97, 95% CI = 0.52–1.81, I 2 = 91%, N = 2,919) based on a random effect model. Karra et al ( 40 ) found that contraceptive use after 2 years of intervention exposure increased by 5.9 percentage points compared with the control group. Of the two remaining articles that reported postpartum contraception, neither showed a statistically significant difference in interventions associated with any contraceptive uptake at 6–9 months or 12–14 months postpartum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After combining these two studies, the meta-analysis showed no significant associations with interventions (OR = 0.97, 95% CI = 0.52–1.81, I 2 = 91%, N = 2,919) based on a random effect model. Karra et al ( 40 ) found that contraceptive use after 2 years of intervention exposure increased by 5.9 percentage points compared with the control group. Of the two remaining articles that reported postpartum contraception, neither showed a statistically significant difference in interventions associated with any contraceptive uptake at 6–9 months or 12–14 months postpartum.…”
Section: Resultsmentioning
confidence: 99%
“…Leave-one-out influence analyses indicated that the findings of the meta-analysis did not rely on a particular study. However, one study in Malawi ( 40 ) reported the intervention group’s hazard of repeat pregnancy was significantly lower during 24 months postpartum.…”
Section: Resultsmentioning
confidence: 99%
“…We use three waves of longitudinal data that were collected as part of a randomized controlled trial of a family planning intervention in urban Malawi that was conducted between 2016 and 2019; a more detailed description of the study design and data collection approach is presented elsewhere (28,29). As part of the trial, 2,143 women who were either pregnant or immediately postpartum (within 6 months of their last live birth), between the ages of 18 and 35, and living in Lilongwe, the capital, were recruited in 2016.…”
Section: Datamentioning
confidence: 99%
“…However, in developing countries, over 200 million women who wish to avoid next pregnancy lack access to their preferred choice of FP method. Therefore, provision of choice for women is important to promote the use of family planning [14] [15]. In Uganda the national mCPR stands at 35% with high-unmet need for FP at 25% (UDHS, 2016).…”
Section: Introductionmentioning
confidence: 99%